(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
A new record of zebra mantis shrimp Lysiosquilla maculata (Fabricius 1793) was confirmed for the first time from the Bay of Bengal, Bangladesh. Morphological and molecular investigations were used to validate this new record. It possesses ten teeth on the dactylus of raptorial claw that can be differentiated easily from its congener species. A partial large subunit ribosomal RNA (16S rRNA) gene sequence was generated and revealed 100% similarity with pre-existing sequences that validated the morphological identification of the species. Including present species, the number of mantis shrimp has increased to nine in Bangladesh. Further extensive study on its biology, ecology, and conservation is highly recommended. J. Bangladesh Acad. Sci. 48(2); 265-271: December 2024